Jorge Burga Bartra - Beingolea Del Carpio, José (2025)
The relationship between profession and life can help us discover the human being. In an environment rife with inequalities, the choice of profession and lifestyle constitutes a socioeconomic and ethnic privilege. Jorge Burga Bartra was born in Trujillo (1941) to a middle-class family; he had the opportunity to develop early intuitions, hobbies, and imaginaries that led him spontaneously and without hesitation to study architecture at the National University of Engineering (UNI), during the years when the epic struggle of the Cuban Revolution motivated students and some teachers.